2019
DOI: 10.1111/sltb.12556
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Measure of Unbearable Psychache

Abstract: Objective Psychache has been proposed to cause suicide when it becomes unbearable. However, existing measures of psychache do not directly target unbearable psychache. Thus, the purpose of the current study was to provide initial validation for a brief measure of unbearable psychache. Method Three items were selected to create the Unbearable Psychache Scale (UP3). Psychometric properties were assessed in two populations: (1) an online sample composed of 1,006 adults (53% male) from various locations in the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 62 publications
3
26
0
Order By: Relevance
“…So far, multiple psychache measures have been compiled and applied in Canada, China, France, Israel, including the Psychache Scale (PAS) (43) (48). Referring to the 13-item PAS, threeitem Unbearable Psychache Scale was developed from items 10, 11, and 12 of the PAS, which also demonstrated excellent internal reliability, strong convergent and predictive validity in psychiatric inpatient adults and general adults (46). In addition, TMPS is the first instrument to assess tolerance for mental pain, which is composed of three aspects: (a) ability to tolerate pain surfeit, (b) belief in the ability to cope with pain, and (c) containing the pain (47).…”
Section: Discussionmentioning
confidence: 99%
“…So far, multiple psychache measures have been compiled and applied in Canada, China, France, Israel, including the Psychache Scale (PAS) (43) (48). Referring to the 13-item PAS, threeitem Unbearable Psychache Scale was developed from items 10, 11, and 12 of the PAS, which also demonstrated excellent internal reliability, strong convergent and predictive validity in psychiatric inpatient adults and general adults (46). In addition, TMPS is the first instrument to assess tolerance for mental pain, which is composed of three aspects: (a) ability to tolerate pain surfeit, (b) belief in the ability to cope with pain, and (c) containing the pain (47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous results with the Portuguese version (Campos et al, 2018) have supported the unidimensional scoring of the scale, its ability to differentiate between individuals at-risk for suicide from individuals not at-risk, its relationship with different, but related, constructs, and its ability to statistically predict suicide ideation. Recently (Pachkowski et al, 2019), Psychache Scale items have been differentiated into 3 items emphasizing unbearable psychache (i.e., unbearable pain) versus 10 items that measure tolerable, rather than unbearable psychological pain. In the current sample, the coefficient α for scores on the total Psychache scale was .93.…”
Section: The Psychache Scalementioning
confidence: 99%
“…The Psychache Scale is composed of 13 items and previous studies (Campos, Holden, & Gomes, 2018;Troister & Holden, 2013) have confirmed its unidimensionality but, recently, Pachkowski, May, Tsai, and Klonsky (2019) have differentiated the scale into three items that emphasize unbearable psychache, a more intense and difficult to tolerate psychological pain (e.g., "I can't take my pain any more") versus 10 items that emphasize a relatively more moderate form of pain (e.g., "I seem to ache inside"). However, those researchers did not evaluate whether the three-item scale of unbearable pain provided a statistically significant incremental contribution to the statistical prediction of suicide behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Unbearable Psychache Scale (UP3) [20], and Tolerance for Mental Pain Scale (TMPS)-10 are the scales used to evaluate the tolerance for mental pain [21,22]. UP3 was developed from 3 items of the Psychache Scale [20].…”
Section: Introductionmentioning
confidence: 99%
“…Unbearable Psychache Scale (UP3) [20], and Tolerance for Mental Pain Scale (TMPS)-10 are the scales used to evaluate the tolerance for mental pain [21,22]. UP3 was developed from 3 items of the Psychache Scale [20]. The TMPS evaluates three aspects of tolerance for mental pain: surfeit of the pain, belief in the ability the cope with the pain, and containing the pain [21,22].…”
Section: Introductionmentioning
confidence: 99%